Synthesis of thiophene-based imine and phosphoazometine compounds: in vitro antiproliferative, antimicrobial, antioxidant, carbonic anhydrase I and II enzyme inhibition evaluations and molecular docking study - Ozturk, Kubra; Tanyildizi, Muhammet Saban; Ciftci, Harun; Aytac, Ozlem Gundogdu (Springer Int Publ Ag, 2025)
New thiophene-based imine ((E)-N,N-dimethyl-4-((thiophen-2-yl-methylene)amino)aniline) (Y6), amine (N1,N1-dimethyl-N4-(thiophen-2)-ylmethyl)benzene-1,4-diamine) (Y6a), and phosphoacomethine (diphenyl (((4-(dimethylamino)phenyl)amino)(thiophen-2-yl)methyl)phosphate) (Y6b) compounds were synthesized, and their structures were thoroughly analyzed. The synthesized compounds were determined to have antioxidant effects and strong inhibitory effects against human carbonic anhydrases I and II (hCA I and hCA II) isoforms. All compounds exhibited significant antioxidant properties, with compound Y6a showing an IC50 value of 5.13 mu g/mL, which was significantly lower than the IC50 of ascorbic acid (17.55 mu g/mL). The compounds also demonstrated potent inhibitory effects against hCA I and hCA II isoenzymes, with IC50 values of 1.96 mu M (Y6), 8.25 mu M (Y6a), and 0.46 mu M (Y6b) for hCA I, and 1.89 mu M (Y6), 0.56 mu M (Y6a), and 1.02 mu M (Y6b) for hCA II. In addition to the experimental findings, molecular docking studies of the synthesized compounds were performed. Antimicrobial tests of the synthesized compounds were performed, and it was determined that they have antibacterial activity against bacterial strains. Additionally, all three compounds exhibited promising antiproliferative activity in the MCF-7 breast cancer cell line, with IC50 values of 56.58 mu M (Y6), 51.30 mu M (Y6a), and 40.01 mu M (Y6b). Notably, the IC50 value of Y6b (40.01 mu M) was found to be comparable to that of cisplatin, one of the effective chemotherapy drugs, and has the potential to be a drug or drug precursor.
Keywords: Phosphanate compound; Antioxidant; Antimicrobial; MCF-7 cells; Carbonic anhydrase